1989
DOI: 10.1302/0301-620x.71b4.2768305
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal flaps in below-knee amputations in Chinese patients

Abstract: Forty-five Chinese patients had below-knee amputation by a sagittal flap technique; 84% for ischaemia. Satisfactory healing was obtained in over 90%, but complications and failure were more common in patients with diabetes mellitus. A modified sagittal flap is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The cross-section of the lower leg is normally not circular but wider anteroposteriorly than mediolaterally. From the perspective of the ratio of flap width to length, Au 6) indicated that the blood flow is more stable in flaps created medially and laterally than in those created anteriorly and posteriorly. Thus, in belowknee amputation, closure using medial and lateral flaps is more advantageous than that using anterior and posterior flaps because of its simpler, easier procedure and more stable blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-section of the lower leg is normally not circular but wider anteroposteriorly than mediolaterally. From the perspective of the ratio of flap width to length, Au 6) indicated that the blood flow is more stable in flaps created medially and laterally than in those created anteriorly and posteriorly. Thus, in belowknee amputation, closure using medial and lateral flaps is more advantageous than that using anterior and posterior flaps because of its simpler, easier procedure and more stable blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…These authors did not discuss the success of this technique in relation to the blood supply (see below). The technique described by Tracey 8 and refined by Au,9 utilises equal-sized sagittal flaps, which include fascia and muscle, on the medial and lateral sides of the calf. These flaps have a larger breadth:length ratio than the conventional posterior flap which is said to account for their superiority.…”
mentioning
confidence: 99%
“…The sagittal flap 8,9 is reported to yield better results because of the cross-sectional anatomy of the calf. Since the sagittal diameter is greater than the coronal diameter, sagittal flaps have a favourable breadth:length ratio.…”
mentioning
confidence: 99%